Extended Inverse Lomax Distribution with Simulation and Application to Crude Birth Rate Data - H. Hadi, Hadi; A. Hilal, Omar; H. Al-Noor, Nadia (Al-Nahrain Journal of Science, 2025)
This paper presents a flexible extended version of the inverse Lomax (EVIL) distribution with four parameters and different shapes of the hazard function. It is developed within the framework of the truncated Rayleigh odd Weibull generator family. Various statistical properties are discussed, including reliability measures, density mixture representation, moments, characteristic and moment-generating functions, quantile function, order statistics, and residual life function with its reversal. The maximum likelihood estimates of unknown parameters are assessed via simulation. The empirical results show that the estimates are reliable and flexible. Furthermore, the EVIL is employed with some competitive distributions to model real-life data concerning the crude birth rate in Iraq. The outcomes of the real data demonstrate that the EVIL outperforms existing inverse Lomax-based models in terms of flexibility and goodness of fit.